Factors That Influence the Event of Low Birth Weight in The Room of Peristi in Tolitoli General Hospitals - Mushalpah, Mushalpah (Journal of Applied Nursing and Health, 2021)
Background: Low birth weight is a public health problem because it is one of the causes of high infant mortality. Factors that can affect LBW include maternal weight, Hb and the age of the mother, which is very important to monitor the health status of children from birth. Objective To determine the factors that influence the incidence of low-birth-weight babies (LBW) in the Hospital Room at Tolitoli General Hospital. Methods: The design used in the study is correlational analytic. Population is all mothers and babies. The sample size was 32 respondents using Purposive sampling techniques. Independent variables of the study were a history of pregnancies with low birth weight, maternal age, anemia. The dependent variable is LBW incidence. Data was collected using a questionnaire, then the data were analyzed using logistic regression tests with a significance level of α ≤ 0.05. Results: The results showed that most of the respondents aged 17-25 years as many as 16 respondents (50%), weight during pregnancy 61-70 kg as many as 17 respondents (53.1%), mothers with Hb> 11 gr / dl during pregnancy as much 26 respondents (81.3%). The results of the study obtained Overall Statistics found that p = 0,000 which means that the independent variables influence together on the dependent variable. If you see the value of p per variable, body weight is p = 0.006, age p = 0.184, Hb p = 0.000, so it can be concluded that the variables that affect the incidence of LBW are maternal weight and Hb during pregnancy. Conclusion: LBW in infants can be caused by maternal weight and Hb or anemic conditions in the mother during pregnancy, this will cause the baby to lack nutritional and energy needs during pregnancy.